2012
DOI: 10.1590/s0100-83582012000200016
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência de controle de Brachiaria brizantha e seletividade dos herbicidas {(diuron + hexazinone) + MSMA } aplicados à cultura da cana-de-açúcar

Abstract: O controle químico é o principal método utilizado no manejo das plantas daninhas em canaviais, sendo utilizados, em sua grande maioria, herbicidas em pós-emergência, os quais podem causar intoxicação à cana-de-açúcar, o que muitas vezes ocasiona redução da produtividade de colmos. No entanto, para diminuir as injúrias de herbicidas em cana-deaçúcar, podem-se reduzir as doses abaixo das recomendadas, desde que aplicadas em condições ambientais adequadas para ainda obter controle satisfatório das comunidades inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This probably occurred because that sample, P6, had been collected in a region of the Paraiba River bordering on a sugarcane plantation (Figure S3 of Supplementary Material ) where diuron pesticide had been sprayed. According to a specialist in agriculture, the diuron pesticide is always applied to young sugarcane plantations, as it is during this period that diuron is most effective in controlling weeds [27]. The other samples were collected in regions of the Paraiba River that are distant from sugar cane plantations.…”
Section: Resultsmentioning
confidence: 99%
“…This probably occurred because that sample, P6, had been collected in a region of the Paraiba River bordering on a sugarcane plantation (Figure S3 of Supplementary Material ) where diuron pesticide had been sprayed. According to a specialist in agriculture, the diuron pesticide is always applied to young sugarcane plantations, as it is during this period that diuron is most effective in controlling weeds [27]. The other samples were collected in regions of the Paraiba River that are distant from sugar cane plantations.…”
Section: Resultsmentioning
confidence: 99%
“…Galon et al (2012) have reported higher sugarcane productivity yields with herbicides as compared to manual weeding.…”
Section: Introductionmentioning
confidence: 99%